Protective effects of brain-targeted dexmedetomidine nanomicelles on mitochondrial dysfunction in astrocytes of cerebral ischemia/reperfusion injury rats. (21st August 2022) - Ge, Shusheng; Zhang, Liwei; Cui, Xiaoguang; Li, Yuan
Highlights: Cerebral ischemia/reperfusion injury (CIRI) is closely related to mitochondrial dysfunction in astrocytes. A kind of brain-targeted dexmedetomidine (Man@Dex) nanomicelles was design based on GLUT1. Man@Dex had the advantages of small particle size, stability and non-toxicity, brain-targeted drug delivery. Man@Dex could improve the activity of injured astrocytes and protect mitochondrial function of damaged astrocytes. Man@Dex could alleviate CIRI and improve MMP, which was beneficial to the recovery of brain injury in rats. Abstract: Cerebral ischemia/reperfusion injury (CIRI) is closely related to mitochondrial dysfunction in astrocytes. Therefore, based on glucose transporter 1 (GLUT1), which is highly expressed in the brain tissue of rats with CIRI, we design a kind of brain-targeted dexmedetomidine (Man@Dex) nanomicelles. The results showed that Man@Dex not only had the advantages of small particle size, stability and non-toxicity, but also realized brain-targeted drug delivery. Primary astrocytes were cultured in vitro to construct CIRI cell model. It was found that Man@Dex could improve the activity of injured astrocytes. Man@Dex could exert antioxidant activity by inhibiting the reactive oxygen species (ROS) production of astrocytes, thus inhibiting the cytotoxicity induced by hypoxia and reoxygenation. Man@Dex could improve the ATP level and mitochondrial membrane potential (MMP) to protect mitochondrial function of damaged astrocytes. The CIRI rat model was constructed and confirmed by hematoxylin and eosin (HE), Triphenyl-2H-tetrazolium chloride (TTC) staining and nerve defect score. It indicated that Man@Dex could alleviate CIRI and improve MMP, which was beneficial to the recovery of brain injury in rats. This research provides a new theoretical basis and target for the development of brain-targeted nano-drugs of CIRI.